Critical evaluation of energy intake data using fundamental principles of energy physiology: 2. Evaluating the results of published surveys. - Black, A; Goldberg, G; Jebb, SA; Livingstone, M; Cole, T; Prentice, A (1991)
The fundamental principles of energy physiology were used to evaluate the validity of reported energy intake (EI) in 37 published dietary studies of adults providing 68 subgroups when classified according to sex and dietary method. EI was expressed as a multiple of BMR estimated using the reported heights and weights of the study populations (EI:BMR(est)). This ratio was compared with a study-specific cut-off value representing the lowest value for EI:BMR(est) that could, within defined bounds of statistical probability, reflect the habitual energy expenditure of a sedentary life-style. Mean EI:BMR(est) was 1.43 (0.19) compared with an expected requirement of 1.55. In 46 out of the 68 groups (68%), EI:BMR(est) was below the study-specific cut-off value. EI:BMR(est) was 1.37 (SD = 0.13) for women and 1.50 (SD = 0.16) for men (P less than 0.001). This could reflect either better reporting by men or a more active life-style. When categorized according to dietary assessment method, 64%, 88% and 25% of results fell below the acceptable cut-off value for studies by diet records, diet recall and diet history, respectively. These data indicate that dietary assessment methods have a strong bias towards underestimation of habitual energy intake.